Analysis of Students’ Higher Order Thinking Skills on Science Subject Using Liveworksheet Argumentative Through Discovery Learning - Hasnunidah, Neni; Amanda, Dhea Olivia; Meriza, Nadya; Lengkana, Dewi; Dewi, Pramita Sylvia (Jurnal Pendidikan MIPA, 2024)
Analysis of Students’ Higher Order Thinking Skills on Science Subject Using Liveworksheet Argumentative Through Discovery Learning. Objective: This research aims to analyze students HOTS on the Classification of Living Creatures material using Liveworksheet argumentative worksheets through the Discovery Learning model at SMP Negeri 1 Natar. Methods: This research is a quasi-experiment with a non-equivalent pretest-posttest control group design. The research subjects were 69 class VII students sampled from a population of 384 people using simple random sampling techniques. Cognitive tests (C4, C5, & C6) were analyzed using the Independent sample t-test. Data on student responses were collected using a questionnaire and analyzed descriptively. Findings: The results of the research show that there is a significant difference in the N-gain value (P<0.05) between learning using the Discovery Learning model and discovery-model based argumentative liveworksheet. The high scores in the experimental class were the evaluate skills (N-gain 0.63) and analyze skills (N-gain 0.62), while in the control class the three HOTS indicators were low. Based on the results of the student response questionnaire, it was found that almost all students (82.25%) gave very positive responses to the use of argumentative lifeworksheets. Conclusion: The liveworksheet effectively improve students' HOTS.        Keywords: HOTS, classification of living things, liveworksheet argumentative worksheet, discovery learning model.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp351-372